Study of the Effect of Endometriosis on AMH Ovarian Stock - محمود, بشار (Latakia University Journal -Medical Sciences Series, 2021)
The study was applied on 168 patients with primary infertility diagnosed endoscopically with documented AMH ovarian stock titre. It was found that most of these patients had a deficiency in the ovarian stock AMH. The aim of the study is to determine the cause of the lack of ovarian reserve AMH, with the aim of taking into account that patients who are late in diagnosis have low ovarian inventory and make the decision for a tube child be late. After 7 months of laparoscopic surgical treatment, the values ​​of AMH in the ovarian stock reached 1.87ng/mm, i.e. a decrease of 26.6% on average, and this decrease was 34.67% in the case of bilateral endometriosis, and 22.33% in the case of unilateral endometriosis. Age was noted as an independent prognostic factor for low AMH and initial AMH titer. The underlying cause of the positive association could be as the increase in the ovarian endothelium increases its toxicity to the ovarian stock and thus the PRIOMDIAL research can contribute and thus increase the AMH levels.